. - JJ, Dharmaraj (Journal of All India Institute of Speech and Hearing, 1970)
Most of us take the ability to produce and understand speech for granted just like the vital process of breathing. But this is a very complex process and plays an important part in the progress of civilization as it provides for exchange of ideas, sharing of experiences and transmitting of knowledge from generation to generation. Impairment of Speech and Hearing can be serious barriers to human communication and self-fulfilment